Formulation and characterization study of itraconazole-loaded microparticles. (8th November 2013) - Segale, Lorena; Giovannelli, Lorella; Mannina, Paolo; Pattarino, Franco
Abstract: The aim of the work was to realize itraconazole-loaded formulations in form of microparticles using a fast, simple and solvent free production procedure. The selected excipients were able to enhance wettability of the final product, to increase drug dissolution rate and to maintain drug in solution thanks to the formation of an emulsified system after contact with the gastrointestinal fluids. Itraconazole formulations contained a structuring lipid, a solubilizing agent and a surface active substance and were prepared by a hot melt method (MMS, melting–milling–sieving). The characterization included drug content determination, granulometric distribution, differential scanning calorimetry (DSC) and in vitro drug release test, physical and technological stability after 12 months of ambient condition storage. The formulations were composed of particles with diameter lower than 355 μm. DSC analysis evidenced that itraconazole was almost completely in the amorphous form; the results of the in vitro drug release tests showed that these formulations were able to increase the rate of the drug release compared to that of the free drug. Stability data showed no significant changes in the thermal and release profiles, confirming that the selected excipients protected the drug avoiding its conversion from amorphous state into crystalline form and maintaining unchanged the delivery behavior.